Antiproliferative activity of xanthones isolated from Artocarpus obtusus - Abd Manaf, Ali (2012)
Abstract An investigation of the chemical constituents in Artocarpus obtusus species led to the isolation of three new xanthones pyranocycloartobiloxanthone A (1). dihydroartoindonesianin C (2). and pyranocycloartobiloxanthone B (3). The compounds were subjected to antiptoliferative assay against human promyelocytic leukemia (HL60) human chronicmyeloid leukemia (K562) and human estrogen receptor (ER+) positive breast cancer (MCF7) cell lines Pyranocycloartobiloxanthone A (1) consistently showed strong cytotoxic activity against the three cell lines compared to the other two with IC50 values of 0.5. 2 0 and 5 0 mu glmL respectively. Compound (1) was also observed to exert antiprolrferative activity and apoptotic promoter towards HL60 and MCF7 cell lines at respective IC50 values The compound (1) was not toxic towards normal cell lines human nontumongenic breast cell line (MCF10A) and human peripheral blood mononuclear cells (PBMCs) with IC60 values of more than 30 mu g/ml.